THE LONG-LASTING POST-COVID SYMPTOM: THE CASE FOR THE EU FISCAL RULES REFORM? - Babin, Mihajlo; Ivanov, Iva; Erić, Miloš (Pravni zapisi, 2022)
The paper investigates compliance with the EU fiscal rules in the period 1992–2020. The EU fiscal rules are prescribed as guidelines and represent a typical example of the soft law approach. The negative impact of the soft law approach is more visible after the periods of economic crisis (2008–2009; 2020–2022). The non-compliance with the prescribed ceilings on the level of the budgetary deficit and public debt create instability and various adverse economic effects. In the paper it is shown that existing rules are not adequate for the job they were made for. It is shown that the design and enforcement of the rules are poor, and that actually the European Commission, the watchdog, is in fact a toothless dog. The goal of the paper is to present potential reform alternatives with the aim to contribute to the reestablishment of the sound fiscal framework in the EU. The paper is concluded with the proposal of a completely new approach for the fiscal rules reform – Growth-Enhancement Fiscal Policy Switch (GEFPS).
Keywords: fiscal rules; fiscal policy; Maastricht criteria; reform; EU